2015
DOI: 10.1042/bj20141446
|View full text |Cite
|
Sign up to set email alerts
|

Arc is a flexible modular protein capable of reversible self-oligomerization

Abstract: The immediate early gene product Arc (activity-regulated cytoskeleton-associated protein) is posited as a master regulator of long-term synaptic plasticity and memory. However, the physicochemical and structural properties of Arc have not been elucidated. In the present study, we expressed and purified recombinant human Arc (hArc) and performed the first biochemical and biophysical analysis of hArc's structure and stability. Limited proteolysis assays and MS analysis indicate that hArc has two major domains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 61 publications
(75 reference statements)
7
98
0
Order By: Relevance
“…Arc and viral Gag share key functional features such as membrane binding (Barylko et al, 2018), self-oligomerization of capsid-like protein (Myrum et al, 2015; Ashley et al, 2018; Pastuzyn et al, 2018), RNA-binding and EV-mediated exosomal releases (Ashley et al, 2018; Pastuzyn et al, 2018; Shepherd, 2018). It is still elusive whether other proteins and mRNAs can be also transferred between neurons through similar mechanisms.…”
Section: Rapid Structural Remodeling Of the Spinementioning
confidence: 99%
“…Arc and viral Gag share key functional features such as membrane binding (Barylko et al, 2018), self-oligomerization of capsid-like protein (Myrum et al, 2015; Ashley et al, 2018; Pastuzyn et al, 2018), RNA-binding and EV-mediated exosomal releases (Ashley et al, 2018; Pastuzyn et al, 2018; Shepherd, 2018). It is still elusive whether other proteins and mRNAs can be also transferred between neurons through similar mechanisms.…”
Section: Rapid Structural Remodeling Of the Spinementioning
confidence: 99%
“…Recent studies show that the Arc protein self‐oligomerizes, contains two biochemically distinct domains that flank a disordered region, and originated from the Ty3/Gypsy retrotransposon family (Myrum et al. ; Zhang et al. ).…”
Section: Introductionmentioning
confidence: 98%
“…Synthesis of Arc is required for longterm potentiation (LTP) and long-term depression (LTD), the major cellular mechanisms for synaptic strengthening and weakening, respectively Plath et al 2006;Rial Verde et al 2006;Shepherd et al 2006;Messaoudi et al 2007;Panja et al 2014). Recent studies show that the Arc protein self-oligomerizes, contains two biochemically distinct domains that flank a disordered region, and originated from the Ty3/Gypsy retrotransposon family (Myrum et al 2015;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Arc was identified in a computational search for domesticated retrotransposons harboring Gag-like protein domains (Campillos et al, 2006). Biochemical studies showed that mammalian Arc has a positively charged N-terminal domain (NTD) and a negatively charged Cterminal domain (CTD), separated by a flexible linker (Myrum et al, 2015). Crystal structure analysis of the isolated CTD revealed two lobes, both with striking 3D homology to the capsid (CA) domain of HIV Gag (Zhang et al, 2015).…”
mentioning
confidence: 99%